Tourism Today / A Geographical Analysis - Pearce Douglas (Longman, 1996)
This book systematically analyses the geographical dimensions of tourism, emphasizing general patterns drawn from empirical studies, geographical analysis and theoretical considerations. Acknowledgements, Introduction, Tourism Models, The Demand for Tourist Travel, Patterns of International Tourism, Intro-National Travel Patterns, Domestic Tourist Flows, Measuring Spatial Variations in Tourism, The National and Regional Structure of Tourism, The Spatial Structure of Tourism on Islands, Coastal Resorts and Urban Areas, Implications and Applications and Conclusions, References, Author and Subject and Place Index.